Review article: bile acid diarrhoea – pathogenesis, diagnosis and management. Issue 8 (24th February 2016) - Mottacki, N.; Simrén, M.; Bajor, A.
Summary: Background: Bile acid diarrhoea results from imbalances in the homoeostasis of bile acids in the enterohepatic circulation. It can be a consequence of ileal disease/dysfunction, associated with other GI pathology or can be idiopathic. Aims: To summarise the different types of bile acid diarrhoea and discuss the currently available diagnostic methods and treatments. Results: Bile acid diarrhoea is found in up to 40% of patients diagnosed as having functional diarrhoea/IBS‐D, and in up to 80% of patients who have undergone ileal resection. It is likely under‐diagnosed and under‐treated. In idiopathic disease, errors in regulation feedback of fibroblast growth factor 19 contribute to the development of the condition. Clinical therapeutic trials for bile acid diarrhoea have been used to diagnose it, but the 75 SeHCAT test is the primary current method. It is sensitive, specific and widely available, though not in the USA. Other diagnostic methods (such as serum measurement of the bile acid intermediate 7α‐hydroxy‐4‐cholesten‐3‐one, or C4) have less widespread availability and documentation, and some (such as faecal measurement of bile acids) are significantly more complex and costly. First‐line treatment of bile acid diarrhoea is with the bile acid sequestrant cholestyramine, which can be difficult to administer and dose due to gastrointestinal side effects. These side effects are less prominent in newer agents such as colesevelam, which may provide higher efficacy, tolerability and compliance. Conclusion: Bile acid diarrhoea is common, and likely under‐diagnosed. Bile acid diarrhoea should be considered relatively early in the differential diagnosis of chronic diarrhoea.